Strength and stiffness of floor trusses fabricated from cold-formed steel lipped channels. (15th February 2019) - Dizdar, Çağan; Baran, Eray; Topkaya, Cem
Highlights: Flexural response of cold-formed steel floor trusses is studied experimentally. CFS section thickness and diagonal-chord connection detail are considered as test variables. Elastic analysis overpredicts truss service stiffness due to neglect of connection flexibility. Experimentally determined strain profiles indicate nonuniform strains in truss chords. Considering local buckling of CFS section with unfolded lips results in accurate strength prediction. Abstract: This paper reports findings of an experimental study on floor trusses fabricated from cold-formed steel lipped channel sections. In design, the members of these trusses are generally considered as pin-ended and their capacities are assessed under pure compressive and tensile loads by making use of commonly accepted design specifications. Seventeen full-scale floor trusses were experimentally investigated through four point bending tests. Thickness of lipped channels, number of connection fasteners, and type of diagonal connection were considered as the prime variables. Test results indicate that there are marked differences between the design and measured values in terms of both the strength and stiffness. The service load stiffnesses of the trusses were found to be lower than the stiffnesses obtained using two dimensional truss models due to the neglect of connection flexibility in analysis models. Additional experiments on screw connections were conducted to find out their axial stiffness. The results from connection tests were used to develop analytical expressions which can be used to simulate connection flexibility. Similar to the stiffness, the strength of the trusses were found to be lower than the predicted strength using the pin-ended member under compression approach. In addition, the observed failure modes are markedly different than the code predictions. The sources of these differences were found to arise from the unfolding of lips at the diagonal to chord member connections and the global bending effects. The strength and failure mode of trusses can be more accurately predicted by considering local buckling of channel sections with unfolded lips.